Pengembangan Modul Pencemaran Lingkungan dengan Model Problem Based Learning (PBL) - Anantyarta, Primadya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Student learning independence can be stimulated by providing problems at the beginning of learning that must be solved. One example of a problem for teaching materials is the problem of students' polluted environment. Modules are one type of teaching material that can be designed systematically and used by students in the independent learning process. By applying a problem-based learning model to the environmental pollution learning module, it can be used as teaching material that trains students' learning independence by finding problems for the learning process and achieving learning objectives. This study aims to develop and determine the feasibility of a problem-based learning module on environmental pollution material for junior high school students in grade VII. The model used in developing the module is a model that has the steps of analysis, design, development, implementation, and evaluation (ADDIE). The module material is developed by first analyzing the needs of teaching materials, then continuing with analyzing the curriculum used and collecting materials from various sources. The module is then validated by a material expert who obtained a score of 90% and validation by a media expert who obtained a score of 92.5%. This module has also been tested on grade VII science teachers with a score of 96% and tested on students and obtained a score of 83%. Based on the validation and trial results, this module is included in the category of very suitable for use in learning.